MODAL SOSIAL PETANI MISKIN DALAM STRATEGI BERTAHAN HIDUP DI KABUPATEN MINAHASA - Charles Reijnaldo Ngangi; Lyndon Reindhart Jacob Pangemanan; Tommy Ferdy Lolowang (Sam Ratulangi University, 2021)
This study aims to study social capital in the survival strategies of poor farmers. The research was conducted for 6 months, from April to October 2020, with the research location in Minahasa Regency. This research was designed descriptively, with a survey method. Sampling was selected purposively on farmers in Minahasa district with 100 farmers as respondents. The data collected in this study are primary and secondary data. Primary data were collected directly through in-depth interviews with farmers. The results showed that the stronger the farmer's social capital, the better his survival strategy. On the other hand, the weaker the social capital, the poor farmer's survival strategy was getting worse.